Edible skin coating material containing neither ammonia nor morpholine - Ali, M Azhar; Zulfiqar, Adnan; Arif, Atta M (Journal of Postharvest Technology, 2017)
Ammonia and morpholine have been widely used in fruit coatings as a base to ionize fatty acids, all over the world. However, both have  certain limitations now. Morpholine is banned in most countries due to its carcinogenic effects and ammonia based waxes are difficult to make  owing to its high volatility. It also causes environmental hazard/irritation for the workers of the waxing factory. So an edible skin coating  material without ammonia and morpholine was made in present research. The edible skin coating material was made from ethanol based  microemulsion of castor oil, shellac, gum rosin and gum acacia, by atmospheric method. A new laboratory method was developed in the  course to prepare an environment friendly edible skin coating material. The newly developed edible skin coating material was applied to  mandarins where it successfully reduced the rate of weight loss, decrease in firmness and vitamin C, with better sensory qualities than the  uncoated ones. It was also environment friendly for workers of waxing factory than the ammonia based fruit coating. The edible skin coating  material was also successfully tested on cucumber and bell-pepper. It could be concluded from the results that good edible skin coating  material can be made without ammonia or morpholine.
Keywords: Ammonia; edible skin coating material; ethanol,; fruit coating; mandarins